Long-term vitamin D deficiency in older adult C57BL/6 mice does not affect bone structure, remodeling and mineralization. Issue 164 (November 2016) - van der Meijden, K.; Buskermolen, J.; van Essen, H.W.; Schuurman, T.; Steegenga, W.T; Brouwer-Brolsma, E.M.; Langenbach, G.E.J.; van Ruijven, L.J.; den Heijer, M.; Lips, P.; Bravenboer, N.
Abstract: Animal models show that vitamin D deficiency may have severe consequences for skeletal health. However, most studies have been performed in young rodents for a relatively short period, while in older adult rodents the effects of long-term vitamin D deficiency on skeletal health have not been extensively studied. Therefore, the first aim of this study was to determine the effects of long-term vitamin D deficiency on bone structure, remodeling and mineralization in bones from older adult mice. The second aim was to determine the effects of long-term vitamin D deficiency on mRNA levels of genes involved in vitamin D metabolism in bones from older adult mice. Ten months old male C57BL/6 mice were fed a diet containing 0.5% calcium, 0.2% phosphate and 0 ( n  = 8) or 1 ( n  = 9) IU vitamin D3 /gram for 14 months. At an age of 24 months, mice were sacrificed for histomorphometric and micro-computed tomography (micro-CT) analysis of humeri as well as analysis of CYP27B1, CYP24 and VDR mRNA levels in tibiae and kidneys using RT-qPCR. Plasma samples, obtained at 17 and 24 months of age, were used for measurements of 25-hydroxyvitamin D (25(OH)D) (all samples), phosphate and parathyroid hormone (PTH) (terminal samples) concentrations. At the age of 17 and 24 months, mean plasma 25(OH)D concentrations were below the detection limit (<4 nmol/L) in mice receiving vitamin D deficient diets. Plasma phosphate and PTH concentrations did not differ between both groups. Micro-CT and histomorphometric analysis of bone mineral density, structure and remodeling did not reveal differences between control and vitamin D deficient mice. Long-term vitamin D deficiency did also not affect CYP27B1 mRNA levels in tibiae, while CYP24 mRNA levels in tibiae were below the detection threshold in both groups. VDR mRNA levels in tibiae from vitamin D deficient mice were 0.7 fold lower than those in control mice. In conclusion, long-term vitamin D deficiency in older adult C57BL/6 mice, accompanied by normal plasma PTH and phosphate concentrations, does not affect bone structure, remodeling and mineralization. In bone, expression levels of CYP27B1 are also not affected by long-term vitamin D deficiency in older adult C57BL/6 mice. Our results suggest that mice at old age have a low or absent response to vitamin D deficiency probably due to factors such as a decreased bone formation rate or a reduced response of bone cells to 25(OH)D and 1, 25(OH)2 D. Older adult mice may therefore be less useful for the study of the effects of vitamin D deficiency on bone health in older people.